The Phenomenon of Siri Marriage in Indonesia: A Review of Munakahat Fiqh - Nurhayatul Hasanah; Niskaromah (Zabags International Journal of Islamic Studies, 2025)
Unregistered (siri) marriage, which refers to a marriage that is religiously valid but not officially registered within the state administration, has become a significant phenomenon in Indonesia. This issue draws attention from both the perspective of Islamic law and the national legal system, due to the ambiguity surrounding the legal status of the wife and children born from a siri marriage, as well as the social impacts it generates. This study aims to analyze the phenomenon of siri marriage within the context of fiqh munakahat, utilizing an approach that integrates the study of Islamic law, positive law, and the social realities of Indonesian society. The research employs a qualitative method with an in-depth literature review of both classical and contemporary fiqh literature, as well as Indonesian legislation related to marriage. The findings indicate that, although siri marriage is religiously valid, it is inconsistent with national regulations that require marriage registration as a condition for legal validity